Health information seeking and people with disability: A systematic search and scoping review. Issue 1 (January 2021) - French-Lawyer, Jeremy; Siano, Steven; Ioerger, Michael; Young, Virginia; Turk, Margaret A.
Abstract: Background: Health information and access to it are important aspects of maintaining health. There are 61 million people with disability in the U.S., many of whom experience health disparities. However, it may not be clear to health professionals how people with disability seek health information. Objective: Assess the breadth, examine the characteristics, and evaluate the risk of bias in the existing literature related to health information seeking and people with disability. Methods: The authors conducted a systematic search across five databases (Pubmed, Scopus, PsycINFO, HealthSTAR, and CINAHL) to identify empirical journal articles related to health information seeking among people with disability. Analysis of data items and a quality assessment were completed. Results: Forty-two articles met the criteria for inclusion and were assessed. The articles primarily used survey methodology (50%), and primarily focused on ten disability types, including MS (19%), CP (17%) and general disability (17%). The articles primarily investigated the internet (88%), and healthcare providers (71%) as sources of health information. Trustworthiness (31%), accuracy (29%), and accessibility (29%) were also commonly assessed. The overall quality was high, with room for improvement in minimizing bias. Conclusions: The literature addressing health information seeking among people with disability is heterogeneous, but generally of high quality. Future research may benefit from an inclusive definition of disability and a more consistent definition of health information. Focused research on best practices and interactions among sources of health information would be valuable additions.